City Structure, Job Search, and Labor Discrimination. Theory and Policy Implications - Harris Selod; Yves Zenou (The Research Institute of Industrial Economics (IUI), 2004)
We consider a search-matching model in which black workers are discriminated against and the job arrival rates of all workers depend on social networks as well as distance to jobs. Location choices are driven by the racial preferences of households (both blacks and whites) consciously choosing to trade off proximity to neighbors of similar racial backgrounds for proximity to jobs. Because of coordination failures in the location choices, multiple urban equilibria emerge. There is a Spatial-Mismatch Equilibrium in which blacks reside far away from jobs and experience high unemployment rates and a Spatial-Match Equilibrium in which blacks are closer to jobs and experience lower unemployment rates. Under some reasonable condition, we demonstrate that all workers are better off in the Spatial-Match Equilibrium. We then consider two policies: affirmative action, and employment subsidies to the firms which hire black workers. We show that the optimal policy requires imposing larger quotas or subsidies in cities in which black workers reside far away from jobs than in cities in which they live closer to jobs.
Keywords: J15; J41; R14; 330; Spatial Mismatch; Racial Preferences; Social Networks; Affirmative Action; Employment Subsidies; Stadtgeographie; Arbeitsplatzsuchmodell; Arbeitsmarktdiskriminierung; Schwarze; Stadt-Land-Beziehung; Theorie; USA